The use of corpus tools in teaching academic writing to EFL students - Utami Rosalina; Davlatova Nargis Dilafruz (Journal of Research in English Language Teaching and Linguistics, 2026)
The use of corpus tools in teaching academic writing has become increasingly important in supporting EFL learners to produce accurate and contextually appropriate texts. While existing studies highlight the benefits of corpus tools in providing authentic language input and improving linguistic accuracy, limited research has explored how students engage with these tools and how such interaction shapes their writing decisions and awareness. This study aims to examine students’ engagement with corpus tools and their influence on academic writing development. Using a qualitative case study design, the study involved 19 EFL students in an advanced academic writing course in Indonesia. Data were collected through students’ written texts, reflective surveys, and semi-structured interviews, and analyzed thematically with triangulation to ensure credibility. The findings show that students mainly engage in querying and exploring corpus data to address immediate writing needs, particularly in collocation, vocabulary, and grammar. Corpus use improves vocabulary choice, grammatical accuracy, argument development, and academic tone, while gradually enhancing students’ awareness from noticing patterns to reflecting on writing decisions. However, deeper engagement such as application and evaluation remains limited. These results suggest that corpus tools effectively support writing accuracy and awareness, but require structured guidance to promote deeper and more reflective use in academic writing development.